Recurrent Polymorphic Ventricular Tachycardia Treated by Ablation of Purkinje Arborization within an Infarct Border-Zone - Park, Kyoung-Min (Texas Heart Institute, 2011)
A 70-year-old patient with 3-vessel coronary artery disease and a left ventricular aneurysm underwent coronary artery bypass grafting, together with a surgical anterior ventricular endocardial restoration (SAVER) procedure. Four days later, he suddenly developed recurrent sustained and nonsustained polymorphic ventricular tachycardia, preceded by monomorphic ventricular premature contractions, and did not respond to any antiarrhythmic drug, including lidocaine, esmolol, or amiodarone. Repeated electrical cardioversion procedures were performed (28 in total). Mapping was performed to target the earliest site of activation in the left ventricle during the ventricular premature contractions, a site where the premature beats were preceded by Purkinje potentials. That site was located along a scar border-zone. Ablation at that site resulted in the disappearance of the monomorphic ventricular premature contractions and in the complete suppression of the electrical storm. These findings appear to indicate that the area in which the Purkinje potentials were recorded along the scar border-zone played an important role in the mechanism of the polymorphic ventricular tachycardia after myocardial infarction.